2006
DOI: 10.1186/1747-597x-1-12
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between interpersonal dynamics, treatment barriers, and larger social forces: an exploratory study of drug-using couples in Hartford, CT

Abstract: Background: The drug treatment field tends to place emphasis on the individual rather than the individual in social context. While there are a growing number of studies indicating that drug-using intimate partners are likely to play an important role in determining treatment options, little attention has been given to the experience and complex treatment needs of illicit drug-using (heroin, cocaine, crack) couples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 50 publications
(42 reference statements)
1
31
0
1
Order By: Relevance
“…Our findings of strong to moderate associations between the enabling factors and gender in this report are consistent with other national surveys (Brady & Ashley, 2005;Mulder et al, 2000;Simmons, 2006). In our study, women identified two major barriers: treatment affordability and availability.…”
Section: Gender and Enabling Characteristicssupporting
confidence: 95%
“…Our findings of strong to moderate associations between the enabling factors and gender in this report are consistent with other national surveys (Brady & Ashley, 2005;Mulder et al, 2000;Simmons, 2006). In our study, women identified two major barriers: treatment affordability and availability.…”
Section: Gender and Enabling Characteristicssupporting
confidence: 95%
“…Turning first to formal support, all but two T2 women entered treatment shortly after their partners were incarcerated, and about half of the T1 women entered treatment during the follow-up period. As Simmons' (2006) research suggests, partner incarceration seems to have created a space in which women in our sample could engage in treatment free from concerns about their partners' responses or activities and about whether their recovery would be damaged by their partners' ongoing use. Additionally, women's decision to enter treatment may have been strengthened by the crises unfolding simultaneously in multiple domains of their lives: past research suggests that feeling "out of control" catalyzes treatment entry among women (Green, Polen, Dickinson, Lynch, & Bennett, 2002;Kaskutas, 1996).…”
Section: Discussionmentioning
confidence: 96%
“…Payne found that several drug-using women began injecting drugs after their partners were imprisoned (Payne, 2007). In contrast, Simmons found that women often entered drug treatment when their partners were incarcerated (Simmons, 2006). While these studies generated divergent results on the surface, they suggest a common underlying conclusion: losing a partner to prison powerfully affects women's substance use.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations